Overview The Presence of Plumbum Urine In Women Operators and Non-Operators of Fuel Oil Pump Wells (SPBU) in Padang City - Fitrayeni, Fitrayeni; Insani, Aldina Ayunda; Iffah, Uliy (Universitas Andalas, 2024)
Introduction: Gas station operators are a group of workers who are at risk of exposure to lead, also known as the heavy metal lead, which can poison the human body in the long term. Objective: This study aims to determine the description of lead levels in the blood of gas station operator officers in Padang City. Methods: This type of research is descriptive with a cross sectional approach, with 20 subjects as gas station operators in Padang City and using a sampling technique, namely consecutive sampling. The research began by providing informed consent and a questionnaire. Next, the lead levels in the respondent's urine were checked using an Atomic Absorption Spectrophotometer. Result: A total of 20 respondents from gas station operators in Padang City, who were willing and met the requirements for sample inclusion criteria, which had been determined by the researcher. (MBIE, 2013). The data obtained is presented in descriptive and tabular form. Conclusion: Lead levels in urine Female officer operating a fuel oil well pump (SPBU) in Padang City has not exceeded the set safe limit